Participation and social services local intervention in spain - Enrique Pastor Seller (Social Work & Society, 2016)
This article presents an analysis of the range opportunities for citizens' participation, in general, and of the social entities in particular - i.e. associative participation - in the design, implementation, follow-up and assessment of the public policies directing care services at a local level in Spain, as well as their possible influence on the agenda and management of local public policies for social welfare. The results of this research allow us to present a theoretical and regulatory framework of what is happening at a European and national level, as well as giving details about the autonomous regions of Spain. In the case of the autonomous communities, we must highlight the changes that new Social Services laws have brought about in terms of widening citizens' participation and opening up feedback for users of the system at a local level. In addition, this article discusses the role of different typologies and offer of mechanisms, bodies and process of participation in the design, management and assessment of social welfare policies at a local level. Finally, we determine the factors that help to increase the efficiency of social public policies, by means of an increase in citizens' participation in local governance. -- En este artículo se presenta un análisis del rango de oportunidades para la participación de los ciudadanos, en general, y de las entidades sociales en particular - es decir, de participación asociativa - en el diseño, implementación, seguimiento y evaluación de las políticas públicas que dirigen los servicios de atención a nivel local nivel en España, así como su posible influencia en la agenda y gestión de las políticas públicas locales para el bienestar social. Los resultados de esta investigación nos permiten presentar un marco teórico y normativo de lo que está sucediendo a nivel europeo y nacional, así como dar detalles acerca de las comunidades autónomas de España. En el caso de las comunidades autónomas, hay que destacar los cambios que las nuevas leyes de servicios sociales provocan en términos de ampliación de la participación de los ciudadanos y la apertura de la retroalimentación de los usuarios del sistema a nivel local. Además, este artículo discute el papel de diferentes tipologías y oferta de los mecanismos, órganos y procedimientos de participación en el diseño, gestión y evaluación de las políticas de bienestar social a nivel local. Por último, determinar los factores que ayudan a aumentar la eficiencia de las políticas públicas sociales, por medio de un aumento de la participación de los ciudadanos en el gobierno local.